Determinants of account receivable and its optimal level: An empirical test on Vietnamese companies - Nhung Do Hong; Tu Tran Thi Thanh; Huong Tran Thi Dieu; Dick Beason (My University, 2019)
Determinants of account receivable and its optimal level: An empirical test on Vietnamese companies
Keywords: Accounts receivable; Optimal level; Vietnamese companies